Effect of Preparation Technique on Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration Sample Adequacy: 3 Years of Experience from a Single Center - Dilek ECE; Gonca GEÇMEN; Şermin KÖKTEN; Sevda ŞENER CÖMERT (Federation of Turkish Pathology Societies, 2019)
Objective: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is increasingly used to sample mediastinal lymph nodes and lesions. However, the methodological details of an optimal preparation technique for aspirated material have not yet been clearly determined. This study was an evaluation of the effect of 2 preparation techniques on the adequacy of aspirated specimens. Material and Method: A retrospective analysis was performed of EBUS-TBNA samples obtained at the institution over a total of 36 months. Two periods were examined. Almost all of the aspirated material was smeared onto slides and fixed with 95% alcohol in the first period of the study. Subsequently, to improve diagnostic ability, a pair of slides was prepared from each needle pass: the first was air-dried, and the second was fixed in 95% alcohol. The remainder of the aspirate was kept for cell block analysis. Results: In total, 462 samples were obtained from 260 patients. The overall sampling adequacy was 74% in the first and 81.1% in the second period (p<0.05). Approximately 14% of the specimens included a sufficient number of cells for immunohistochemical cell block evaluation in the first period and 42% in the second period (p<0.001). Histological subtyping of non-small cell lung carcinoma was determined in 18 (56.3%) and the primary origin of a tumor was determined based on morphological and immunohistochemical properties in 32 (84.2%) of the patients in the first and second periods, respectively. Conclusion: The access to a sufficient EBUS-TBNA sample and the ability to perform the appropriate preparation can impact the specific diagnosis and treatment of patient with a single procedure.